Diaghilev and British Writing - Jones, Susan (Edinburgh: Edinburgh University Press, 2009)
RESUMEN: This article explores the diversity of British literary responses to Diaghilev's project, emphasising the way in which the subject matter and methodologies of Diaghilev's modernism were sometimes unexpectedly echoed in expressions of contemporary British writing. These discussions emerge both in writing about Diaghilev's work, and, more discretely, when references to the Russian Ballet find their way into the creative writing of the period, serving to anchor the texts in a particular cultural milieu or to suggest contemporary aesthetic problems in the domain of literary aesthetics developing in the period. Figures from disparate fields, including literature, music and the visual arts, brought to their criticism of the Ballets Russes their individual perspectives on its aesthetics, helping to consolidate the sense of its importance in contributing to the inter-disciplinary flavour of modernism across the arts. In the field of literature, not only did British writers evaluate the Ballets Russes in terms of their own poetics, their relationship to experimentation in the novel and in drama, they developed an increasing sense of the company's place in dance history, its choreographic innovations offering material for wider discussions, opening up the potential for literary modernism's interest in impersonality and in the 'unsayable', discussions of the body, primitivism and gender.